**Problem : **
Find the inverse of *f* (*x*) = .

y = |

Solve for

(x - 1)y | = x + 2 | ||

xy - y | = x + 2 | ||

xy - x | = y + 2 | ||

x | = |

Now switch the variables

y = |

**Problem : **
Find the inverse of *f* (*x*) = 6 + 5*x*^{3}.

y | = 6 + 5x^{3} | ||

x | = |

Now switch variables:

y = |

**Problem : **
If *f* (3) = 2 and *f'*(3) = 7, what is (*f*^{-1})'(2)?

**Problem : **
Find (*f*^{-1})'(2) for *f* (*x*) = 4*x*^{3} - 2*x* + 2.

(f^{-1})'(2) | = | ||

= | |||

= - |

**Problem : **
Find (*f*^{-1})'(- 4) for *f* (*x*) = *x*^{3} - *x*^{2} - 4*x*.

Take a Study Break!